Stress and managerial competence of private preschool administrators - Go, Jubille Yap (2006)
This study sought to determine and analyze the personal, school organizational, environmental, and private life stressors affecting the managerial competence of the private preschool administrators. Eighty private preschool administrators from NCR were chosen as respondents to the Preschool Administrator Stress Index (PASI) and the Preschool Administrator Managerial Competency Assessment (PAMCA), both made by the researcher. It was concluded that preschool administrators were generally competent in all facets of managerial competencies, and physically and psychologically adept, but showed behavioral symptoms of being distressed. It was partly accepted that preschool administrators' personal health and manegerial competence are affected by the stressor, socio-demographic, and school variables.